Induksi Kalus Eksplan Daun Stroberi (Fragaria x ananassa Duch) dengan Pemberian NAA dan CaP Secara In Vitro - Millenia, Fauzia Khaerunnisa; Sumadi, S; Suminar, Erni; Nuraini, Anne; Pitaloka, Gina Gustiani (Journal Galung Tropika, 2022)
The use of high-yielding strawberry varieties such as Sweet Charlie needs to be followed by proper propagation methods to produce large amounts of strawberry seeds quickly and free from disease. In vitro propagation techniques can be done through the formation of a callus. This study aims to determine the effect of the combination of NAA and CaP treatment on the in vitro induction of the Sweet Charlie strawberry variety leaf callus. This experiment was arranged using a completely randomized design (CRD) which consisted of 9 treatments, namely concentrations of NAA (0 mg L-1, 5 mg L-1, 10 mg L-1) and CaP (0 mgL-1, 1 mgL-1, 2mg L-1) which was repeated three times. The results showed that using NAA 5 mgL-1 was the best treatment to support callus induction of the Sweet Charlie strawberry variety in vitro. The supporting with the parameter percentage of callus formation reaching 100%, callus appearance time at 13.5 days after planting (DAP), callus diameter of 9.00 mm, callus weight of 0.52 g, and the percentage of crumbly textured callus was 50%.